2009
DOI: 10.1124/jpet.109.153163
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol 12-Myristate 13-Acetate Potentiation ofN-Methyl-d-aspartate-Induced Currents in Primary Cultured Cerebellar Granule Cells Is Mediated by Protein Kinase Cα

Abstract: We have previously reported that activation of protein kinase C (PKC) by phorbol 12-myristate 13-acetate (PMA) results in potentiation of N-methyl-D-aspartate-induced currents (I NMDA ) of receptors contained in primary cultured cerebellar granule cells (CGCs). The purpose of this study was to identify which PKC isoform(s) was responsible for this effect by using the wholecell patch-clamp technique. Experiments were conducted on CGCs that expressed both the NR2A and NR2B NMDA receptor subunits as well as the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 37 publications
(68 reference statements)
3
10
0
Order By: Relevance
“…We also reported that similar results could be observed with briefer (12.5 min) PMA exposures, and that increases in I PK could be observed for up to 20 min with repeated agonist exposure clusters during whole-cell recordings (Reneau et al, 2009). In this current study, we corroborate our previous findings in that 100 nM PMA treatment at 37° C resulted in sustained augmentation of I Pk (Figure 1).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…We also reported that similar results could be observed with briefer (12.5 min) PMA exposures, and that increases in I PK could be observed for up to 20 min with repeated agonist exposure clusters during whole-cell recordings (Reneau et al, 2009). In this current study, we corroborate our previous findings in that 100 nM PMA treatment at 37° C resulted in sustained augmentation of I Pk (Figure 1).…”
Section: Resultssupporting
confidence: 66%
“…With this PMA exposure paradigm, small, significant increases in I Pk , with no significant increases in I SS were observed (Popp et al, 2008a). Thus, based on the results from Machu et al, 2006, we incorporated experiments in which CGCs were treated with PMA at physiological temperatures (37° C) and observed robust and significant increases in both I Pk and I SS (Popp et al, 2008a) and have continued to use this exposure paradigm to assess PMA-mediated alterations in I NMDA (Reneau et al, 2009). PMA was diluted and applied in conditioned feeding media.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PKC potentiates NMDA receptor function via phosphorylation (MacDonald et al, 2001). Activation of PKC by phorbol 12-myristate 13-acetate (PMA) shows that PMA-enhanced function of NMDA receptors expressed in primary cultured cerebellar granule cells is mediated by activation of PKCa (Reneau et al, 2009). Activation of PKCa by galantamine enhances NMDAR functionality via phosphorylation of Ser-896 of the NMDAR NR1 subunit (Tingley et al, 1997).…”
Section: Discussionmentioning
confidence: 98%